IDENTIFIKASI BENTENG BONE-BONE DI DESA BONE-BONE KECAMATAN BATUKARA KABUPATEN MUNA - Tamiudin Tamiudin; Abdul Alim; Syahrun Syahrun (SANGIA: Jurnal Penelitian Arkeologi, 2023)
Benteng Bone-Bone is one of the archaeological remains that constitutes a cultural heritage of the Indonesian nation. This research addresses two main problems: (1) what archaeological remains are found within Benteng Bone-Bone, and (2) what is the function of Benteng Bone-Bone based on its archaeological remains? The study aims to identify and explain the archaeological remains at Benteng Bone-Bone and to determine its function based on these remains. The research is grounded in conceptual frameworks such as spatial archaeology, the concept of fortifications, the concept of archaeological remains, and cultural history theory. This qualitative research employs inductive reasoning and is supported by classification analysis and contextual analysis. Based on the findings, it was concluded that there are 11 archaeological remains at Benteng Bone-Bone, consisting of the fort itself, Lawa I, Lawa II, Makam I, Makam II, Makam III, and loose finds in the form of mollusk fragments representing five species: Helix pomatia, Ruditapes decussatus, Pugilina cochlidium, Telescopium, and Cerithidea quoyi. Benteng Bone-Bone served as a defensive fortification.